TEORI ABDUL KARIM SOROUSH: ANALISIS TEORI AGAMA DAN MASYARAKAT BERAGAMA - Miftah arief (Nizham Journal of Islamic Studies, 2022)
Soroush is a Muslim and comes from a society where political discourse and political debate are still struggling to resolve religious relations with politics and therefore the types of arguments and concerns he gives to secular liberal democracy mainly come from that background. Moreover, the implication of Soroush's political theory is that God was ruled out, not because of social evolution and the ability of human beings to manage their lives based on his own knowledge and collective rational consensus, but by deliberate political decisions to expel him from sociopolitical life.